MyPyramid Ways to Fruits and Vegetables for Your Child - Glenda L. Warren (EDIS)
FCS-8866, a 2-page fact sheet by Glenda L. Warren, provides pointers for parents to involve children in shopping for and preparing fruits and vegetables, serve foods in appealing ways, and help children get the best nutrition. Published by the UF Department of Family Youth and Community Sciences, December 2008.